Оцінка ефективності використання змішаної системи технічного обслуговування і ремонту дорожніх транспортних засобів автомобільного транспорту - Рікунов, Олег Миколайович; Кужелович, Віктор Іванович (Національний технічний університет "Харківський політехнічний інститут", 2022)
В статті аргументована актуальність визначення показника ефективності використання змішаної системи технічного обслуговування і ремонту дорожніх транспортних засобів автомобільного транспорту. Аналіз існуючих стратегій технічного обслуговування і ремонту показав, що кожна з них має свої переваги і недоліки. Поєднання переваг кожної зі стратегій і виключення недоліків приведуть до створення змішаної системи технічного обслуговування та ремонту. яка дозволить підвищити готовність дорожніх транспортних засобів автомобільного транспорту, коефіцієнт технічної готовності і коефіцієнт технічного використання, якість експлуатації, знизити витрати на обслуговування і ремонт при заданому рівні надійності техніки.

The article argues the relevance of determining the efficiency of the mixed system of maintenance and repair of road vehicles. Improving the system of maintenance and repair of road transport is one of the main ways to increase the efficiency of motor transport enterprises. This is due to the high growth rate of work performed, the significant complexity of the design of modern vehicles and the variety of implementation of new maintenance strategies and diagnostic methods. Significant complications in the design of components and units of modern road vehicles, increasing their functions, more busy modes of operation of components, units, etc.- significantly exacerbated the problem of traffic safety, which is largely due to the quality of maintenance and repair. The urgent need to improve the system of maintenance and repair is due to changes in the technical condition of automotive equipment and the requirements for maintaining the working condition of vehicles during operation. An analysis of existing maintenance and repair strategies has shown that each has its advantages and disadvantages. The combination of advantages of each strategy and elimination of shortcomings will lead to the creation of a mixed system of maintenance and repair, which along with high-quality staffing of repair companies and equipping them with modern diagnostic equipment will increase the readiness of road vehicles, technical efficiency and efficiency quality of operation, reduce maintenance and repair costs at a given level of reliability.
Evaluation of the efficiency of using a mixed system of maintenance and repair of road vehicles of road transport
Keywords: дорожні транспортні засоби; автомобільний транспорт; система технічного обслуговування; система технічного ремонту; планово-попереджувальна система; середня сумарна тривалість; коефіцієнт технічної готовності; коефіцієнт технічного використання; економічна доцільність; road transport vehicles; maintenance and repair system; preventive maintenance system; average total duration of maintenance and repair; technical readiness coefficient; technical utilization coefficient; economic feasibility